Canadian Perspectives: A Content Analysis of Selected English Language LIS Research - Shamchuk, Lisa (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
To support evidence based decision making, for updating and enhancing authentic Library and Information Studies (LIS) curriculum, or supporting services, programs, and other evaluative practices within various library settings, this exploratory quantitative content analysis examined the scope of Canadian LIS research. In total, 4354 peer reviewed research articles from 25 LIS journals published between 2015-2022, were coded for Canadian content, author affiliation, and sector representation. Percentages of Canadian content and authorship from this point in time analysis align with previous studies, showing that Canadian content and authors are less prevalent compared to those from the USA, with a strong emphasis on academic libraries and academic affiliated authors. A shortlist of key academic journals with significant Canadian representation was also compiled and shared to aid in gathering evidence about Canadian libraries.